Feasibility Analysis of the International Promotion of Wushu Bingdao from the Perspective of the Belt and Road Initiative: A Strategy Exploration Based on Qualitative Research - Li, Guanchong; Zhang, Guodong (Quality in Sport, 2024)
Background: This study aims to explore the feasibility of the international promotion of Wushu Bingdao within the context of the Belt and Road Initiative. As a significant component of traditional Chinese culture, Wushu Bingdao holds potential for cross-cultural exchange. However, its promotion faces multiple challenges in the globalized context, such as cultural differences, a shortage of skilled practitioners, market competition, and the limitations of traditional promotion methods. Methods: Utilizing literature review, expert interviews, and qualitative analysis, this study systematically reviews literature related to the promotion of Wushu Bingdao, analyzing its cultural connotations and historical heritage, and identifying key obstacles to international promotion. Strategic recommendations are proposed to address these challenges. Results: The study reveals that enhancing the understanding of the cultural essence of wushu, developing a specialized team of international promotion professionals, standardizing the Wushu Bingdao system, and employing innovative international communication methods can significantly increase the visibility and influence of Wushu Bingdao globally, facilitating its exchange and development within global cultural diversity. Conclusion: Despite the numerous challenges facing the international promotion of Wushu Bingdao, leveraging the Belt and Road Initiative platform and combining innovative promotion strategies offer the potential for broader recognition and practice of Chinese Wushu Bingdao worldwide.